2002
DOI: 10.1103/physreve.66.067103
|View full text |Cite
|
Sign up to set email alerts
|

From gene families and genera to incomes and internet file sizes: Why power laws are so common in nature

Abstract: We present a simple explanation for the occurrence of power-law tails in statistical distributions by showing that if stochastic processes with exponential growth in expectation are killed (or observed) randomly, the distribution of the killed or observed state exhibits power-law behavior in one or both tails. This simple mechanism can explain power-law tails in the distributions of the sizes of incomes, cities, internet files, biological taxa, and in gene family and protein family frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
169
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(176 citation statements)
references
References 18 publications
(10 reference statements)
4
169
0
3
Order By: Relevance
“…Mathematical models have shown that a system with this description will produce a Pareto distribution (Reed & Hughes, 2002).…”
Section: Control Of Variation By Reward Probability 29 March 2004 Vermentioning
confidence: 98%
“…Mathematical models have shown that a system with this description will produce a Pareto distribution (Reed & Hughes, 2002).…”
Section: Control Of Variation By Reward Probability 29 March 2004 Vermentioning
confidence: 98%
“…Italian economist Vilfredo Pareto (1897) was the first to suggest it followed a "natural law" where the higher end of the wealth distribution is described by power law, P (w) ∼ w −1−α . Repeated empirical studies Levy Solomon (1997); ;Reed Hughes (2002) ;Aoyama Souma (2003) show that the power law tail exhibits a remarkable spatial and temporal stability and while the value of the exponent, α, may vary slightly, it changes little from the value ∼ 1.5.…”
Section: Introductionmentioning
confidence: 99%
“…The same result holds also if the sampled process is not deterministic, but grows exponentially in expectation [561]. This Version 1.0.3, typeset on model has the advantage of producing a heavy-tailed distribution in the transient state, as opposed to previous models that only produce such distributions asymptotically.…”
Section: End Boxmentioning
confidence: 48%
“…One such model postulates that the probability that a new page links to an existing one is proportional to the number of links the page already has [49,9]. Another more abstract model considers the observed system state as resulting from sampling individual processes that each grow exponentially [352,561] (or similarly, from an exponentially growing number of sources that each grows exponentially [207]). …”
Section: Usesmentioning
confidence: 99%
See 1 more Smart Citation